2017
DOI: 10.7127/rbai.v11n700665
|View full text |Cite
|
Sign up to set email alerts
|

Características Biométricas E Acúmulo De Fitomassa Da Berinjeleira Sob Irrigação Com Água Residuária E Doses De Nitrogênio E Fósforo

Abstract: RESUMOA água na região semiárida é um dos recursos naturais com maior escassez, sendo imprescindível o seu manejo correto e a prática do reuso. Neste contexto, propôs-se avaliar o uso de nitrogênio e fósforo junto com água residuária doméstica pós-tratada em filtro de areia com fluxo intermitente sobre os aspectos de crescimento e acúmulo de fitomassa de plantas de berinjela cultivadas em casa de vegetação no semiárido paraibano. O experimento foi conduzido no município de Pombal, Paraíba, utilizando-se o deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 11 publications
3
12
0
7
Order By: Relevance
“…In relation to the test of comparison between means, it was verified that the different types of water used in the irrigation of the plants (WW and IW) provided significant effects on all variables of okra production (Table 4). These results confirmed the reports of Kummer et al (2017) and Medeiros et al (2015Medeiros et al ( , 2017, where they stated that part of the nutritional requirements of crops can be supplied by nutrients present in the wastewater itself. Note.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…In relation to the test of comparison between means, it was verified that the different types of water used in the irrigation of the plants (WW and IW) provided significant effects on all variables of okra production (Table 4). These results confirmed the reports of Kummer et al (2017) and Medeiros et al (2015Medeiros et al ( , 2017, where they stated that part of the nutritional requirements of crops can be supplied by nutrients present in the wastewater itself. Note.…”
Section: Resultssupporting
confidence: 82%
“…The results obtained in this study confirmed the information provided by the other authors, Medeiros et al (2015), Sousa (2015), Kummer et al (2017), and Medeiros et al (2017) when they reported that WW is a nutritional source for plants, especially macronutrients, which promotes the reuse of nutrients by crops. Note.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations